The analysis ability of technological content knowledge (TCK) of biology educations students in Universitas Ahmad Dahlan in preparation of learning plan - Wahyu Oktamarsetyani; Paidi Paidi (Universitas Ahmad Dahlan, 2019)
Technological Content Knowledge is the students (prospective biology teachers) knowledge in determining certain technologies that will be used in the learning process. This knowledge is important for prospective teachers, because it can help students in understanding the material that has been conveyed. The objective of this study is to examine the ability of Technological Content Knowledge (TCK) of biology educations students in preparing learning plans. The study is a quantitative descriptive research by using survey method. Participants of this study are all biology educations student a total of 120 students in Faculty of teacher training and education in Universitas Ahmad Dahlan 6th semester academic year 2017/2018. Data collection techniques use non-test instrument of the learning plan document observation sheet and the instrument on the written tests about technological knowledge and biological content. The data obtained is statistically analyzed in a descriptive form intended to figure out the capabilities of the TCKs student. In order to the acquired results can be trusted and reduce subjectivity, a compatibility test is conducted between panelists. The results showed that: (1) biology education students have TCK ability which is less than reviewed for learning plan, (2) biology education students have TCK skills worth in terms of written test result about TCK knowledge.